Prostate cancer characteristics in the World Trade Center cohort, 2002–2013. Issue 4 (July 2018) - Hashim, Dana; Boffetta, Paolo; Galsky, Matthew; Oh, William; Lucchini, Roberto; Crane, Michael; Luft, Benjamin; Moline, Jaqueline; Udasin, Iris; Harrison, Denise; Taioli, Emanuela
Abstract : An increased incidence of prostate cancer was reported in three cohorts of World Trade Center (WTC) respondents. It is uncertain whether this increase is because of WTC-related exposures or enhanced surveillance. Prostate cancer cases (2002–2013) were obtained from the WTC Health Program. Age, race, and Gleason score distribution were compared with New York State Cancer Registry cases from the same time period. Multivariate models were adjusted for age and race. Analyses of clinical characteristics of prostate cancer cases within the cohort were also carried out, adjusting for age, race, and WTC exposure categories. WTC respondents had a prostate cancer age-standardized rate ratio of 1.65 [95% confidence interval (CI): 1.37–1.93] compared with New York State; age-specific ratios were highest for ages 30–49 (2.28; 95% CI: 1.51–3.43), 70–74 (2.05; 95% CI: 1.03–4.10), and 80–84 years (5.65; 95% CI: 1.41–22.58). High WTC exposure was associated with advanced clinical stage (5.58; 95% CI: 1.05–29.76; P trend =0.03). WTC respondents continue to have a higher prostate cancer rate compared with New York State as a whole. Respondents with a higher WTC exposure level may have had more advanced clinical stage of prostate cancer.